2016
DOI: 10.1002/ijc.29985
|View full text |Cite
|
Sign up to set email alerts
|

Exploring circulating micro‐RNA in the neoadjuvant treatment of breast cancer

Abstract: Breast cancer is the most frequently diagnosed malignancy amongst females worldwide. In recent years the management of this disease has transformed considerably, including the administration of chemotherapy in the neoadjuvant setting. Aside from increasing rates of breast conserving surgery and enabling surgery via tumour burden reduction, use of chemotherapy in the neoadjuvant setting allows monitoring of in vivo tumour response to chemotherapeutics. Currently, there is no effective means of identifying chemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 138 publications
(207 reference statements)
0
30
0
Order By: Relevance
“…This indicates that the serum N ‐glycome reflects the body's response to surgery as well as to the removal of the tumour. Glycosylation changes in serum N ‐glycome could therefore serve as biomarker for response to treatment, particularly neoadjuvant chemotherapy and surgery (Casey et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This indicates that the serum N ‐glycome reflects the body's response to surgery as well as to the removal of the tumour. Glycosylation changes in serum N ‐glycome could therefore serve as biomarker for response to treatment, particularly neoadjuvant chemotherapy and surgery (Casey et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Glycosylation changes in serum N-glycome could therefore serve as biomarker for response to treatment, particularly neoadjuvant chemotherapy and surgery (Casey et al, 2016).…”
Section: Responders Show Bigger Glycosylation Changes With Chemotheramentioning
confidence: 99%
“…Here we report that distinctly altered patterns of circulating miR expression are observed in patients after treatment with dovitinib. Plasma miRs have a major potential as cancer biomarkers [32][33][34]. MiRs are deregulated as a result of the uncontrolled cell proliferation, stromal remodeling and immune regulation that define cancer and are stably exported into the circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that some miRNAs are associated with prognosis in Her-2 positive BC [13,14] . The circulating miRNAs can be as chemotherapeutic response predictors, prognosticators or potential therapeutic targets [15] . Gu X et al found that the relative expression level of miR-451 was lower in the neoadjuvant chemotherapy resistant BC patients, suggesting the circulating miR-451 may have a functional significance in predicting the resistance to neoadjuvant chemotherapy in BC patients [16] .…”
Section: Introductionmentioning
confidence: 99%